Evaluation Measures for Preference Judgments - Carterette, Ben; Bennett, Paul (Poster-Paper in Proceedings of the 31st Annual International ACM SIGIR Conference on Research and Development in Information Retrieval, 2008)
There has been recent interest in collecting user or assessor preferences, rather than absolute judgments of relevance, for the evaluation or learning of ranking algorithms. Since measures like precision, recall, and DCG are deﬁned over absolute judgments, evaluation over preferences will require new evaluation measures that explicitly model them. We describe a class of such measures and compare absolute and preference measures over a large TREC collection.